Guinea : Staff Report for the Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report, 2002)
This paper examines Guinea's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). The first review of the third annual program supported by the PRGF was completed on December 20, 2000. Progress was made on the structural front, but the public enterprise restructuring and privatization program continues to experience delays. The new program focuses on maintaining macroeconomic stability and accelerating growth as prerequisites for poverty reduction, consistent with the Interim Poverty Reduction Strategy Paper (I-PRSP).